2016
DOI: 10.1111/jav.00942
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infection negatively affects feather growth rate in the house sparrowPasser domesticus

Abstract: Birds often face various stressors during feather renewing, for example, enduring infection with blood parasites. Because nutritional resources are typically limited, especially for wild animals, when an individual allocates energy to one physiological system, there is subsequently less for other processes, thereby requiring a trade‐off. Surprisingly, potential trade‐offs between malaria infection and feather growth rate have not been experimentally considered yet. Here, we conducted three studies to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
(118 reference statements)
4
24
1
1
Order By: Relevance
“…This result should be therefore considered with this caveat in mind. The finding of a reduction of feather growth rate in birds infected by haemosporidians is consistent with the few previous studies investigating this relationship (Marzal et al 2013a, b, Coon et al 2016 and shows that haemosporidian infection can impair a major life-history event, moult, with potentially severe negative consequences for feather morphology, and thus flight performance. The reason why such effect was detected only for older individuals is open to speculation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result should be therefore considered with this caveat in mind. The finding of a reduction of feather growth rate in birds infected by haemosporidians is consistent with the few previous studies investigating this relationship (Marzal et al 2013a, b, Coon et al 2016 and shows that haemosporidian infection can impair a major life-history event, moult, with potentially severe negative consequences for feather morphology, and thus flight performance. The reason why such effect was detected only for older individuals is open to speculation.…”
Section: Discussionsupporting
confidence: 91%
“…We expected that infection affected feather growth rate because this effect has been shown in the few studies where it has been investigated so far (Marzal et al 2013a, b, Coon et al 2016) and malarial infection has been shown to affect the progress of moult (Morales et al 2007, Tarello 2007, but see Allander and Sundberg 1997). The rate of growth of the feathers during moult is sensitive to physiological state of the birds, and poor body conditions are reflected in reduced growth rate (Yosef andGrubb 1992, Takaki et al 2001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Parasitism may also affect the condition of birds and, hence, the rate at which they grow new feathers (Coon et al ). To measure feather growth rate, we plucked the third tail feather (R3), counting inward from the outermost right tail feather, and estimated feather growth rate by measuring the average growth bar width on each tail feather.…”
Section: Methodsmentioning
confidence: 99%
“…For example, several studies have found no deleterious effects of haemosporidian infection on reproductive fitness (Dufva 1996, Bensch et al 2007 or body condition (Ashford 1971, Dufva 1996, Young and Proudfoot 2014, and Zylberberg et al (2015) report a positive correlation of haemosporidian infection on fitness. In contrast, numerous studies have demonstrated that haemosporidian infection can have a negative effect on reproduction (Allander and Bennett 1995, Merino et al 2000, Knowles et al 2010, Asghar et al 2011, feather growth rate (Marzal et al 2013, Coon et al 2016, body condition (Dawson andBortolotti 2000, Marzal et al 2013), telomere-length (Asghar et al 2015), and can cause anemia and death (Valkiūnas 2005, Atkinson and Samuel 2010, Santiago-Alarcon et al 2013). Because of their effects on red blood cells, haemosporidians may have more subtle impacts on fitness via mechanisms such as inhibiting or delaying migration (Valkiūnas 1989, Asghar et al 2011.…”
Section: Introductionmentioning
confidence: 99%